Distal fibular periosteal flap for superior peroneal retinaculum reconstruction - Ahrenholz, Samuel J; Lalevee, Matthieu; Lee, Hee Young; Tazegul, Tutku E; VandeLune, Christian A; Mansur, Nacime Salomão Barbachan; César Netto, César de (Journal of the Foot & Ankle, 2021)
Peroneal tendon instability is a common injury that occurs in physically active individuals, often as a result of trauma and in the context of an anatomically shallow distal fibular groove. Subluxation of these tendons over the lateral malleolus is accompanied by superior peroneal retinaculum injury. Several techniques have been described in the literature, including fibular groove deepening and retinaculum repair, but few reconstruction techniques are available for cases with insufficient residual retinaculum. We report the case of a 53-year-old man, without a history of trauma, who presented with chronic peroneal instability with a completely obliterated, unsalvageable retinaculum which we treated with a combination of fibular groove deepening and fibular periosteal flap to reconstruct the superior peroneal retinaculum. Level of Evidence V; Case Report; Expert Opinion.